Condensation and thermalization of an easy-plane ferromagnet in a spinor Bose gas - Prüfer, Maximilian; Spitz, Daniel; Lannig, Stefan; Strobel, Helmut; Berges, Jürgen; Oberthaler, Markus K. (Nature physics, 2022)
Bose-Einstein condensates are an ideal platform to explore dynamical phenomena emerging in the many-body limit, such as the build-up of long-range coherence, superfluidity or spontaneous symmetry breaking. Here we study the thermalization dynamics of an easy-plane ferromagnet employing a homogeneous one-dimensional spinor Bose gas. We demonstrate the dynamic emergence of effective long-range coherence for the spin field and verify spin-superfluidity by experimentally testing Landau’s criterion. We reveal the structure of one massive and two massless emerging modes—a consequence of explicit and spontaneous symmetry breaking, respectively. Our experiments allow us to observe the thermalization of an easy-plane ferromagnetic Bose gas. The relevant momentum-resolved observables are in agreement with a thermal prediction obtained from an underlying microscopic model within the Bogoliubov approximation. Our methods and results are a step towards a quantitative understanding of condensation dynamics in large magnetic spin systems and the study of the role of entanglement and topological excitations for their thermalization.